Effects of Nitrogen Application Level on Growth and Yield Of Winter Wheat (Bangladesh Journal of Botany, 2023)
In order to achieve higher crop yield and improve the utilization efficiency of nitrogen fertilizer resources. Effect of nitrogen on the tillering ability, the aboveground dry matter mass and yield of winter wheat (WW) during the growing period were analyzed in a field experimental plot of Qinling Field Monitoring Center Station in Baoji City, Shaanxi Province from 2020 to 2021. Results demonstrated that nitrogen use significantly improved the tillering ability of WW during the overwintering and turning green stage; however, the use of nitrogen > 120 kg/hm2 did not have a significant impact on the tillering ability of WW. The growth stages were directly proportional to the extent of aboveground dry matter accumulation (DMA) of WW and were found to be maximum at maturity. Greater usage of nitrogen significantly enhanced aboveground DMA before the jointing stage, but nitrogen application as high as 270 kg/hm2 was not conducive to the aboveground DMA after the jointing stage. For WW, at first, the yield increased and then decreased with the increased concentration of nitrogen. When the nitrogen application level was 120 kg/hm2, the highest yield of WW was 7506 kg/ha. However, there was an insignificant increase in yield at nitrogen levels > 120 kg/hm2. In the study area, at nitrogen > 195 kg/hm2, a decrease in yield was observed. Therefore, the recommended nitrogen application level in this area was 120kg/hm2.Bangladesh J. Bot. 51(4): 937-941, 2022 (December) Special